A high abundance of massive galaxies 3-6 billion years after the Big Bang. - Glazebrook, K; Abraham, R; McCarthy, P; Savaglio, S; Chen, H; Crampton, D; Murowinski, R; Jørgensen, I; Roth, K; Hook, I; Marzke, R; Carlberg, R (2004)
Hierarchical galaxy formation is the model whereby massive galaxies form from an assembly of smaller units. The most massive objects therefore form last. The model succeeds in describing the clustering of galaxies, but the evolutionary history of massive galaxies, as revealed by their visible stars and gas, is not accurately predicted. Near-infrared observations (which allow us to measure the stellar masses of high-redshift galaxies) and deep multi-colour images indicate that a large fraction of the stars in massive galaxies form in the first 5 Gyr (refs 4-7), but uncertainties remain owing to the lack of spectra to confirm the redshifts (which are estimated from the colours) and the role of obscuration by dust. Here we report the results of a spectroscopic redshift survey that probes the most massive and quiescent galaxies back to an era only 3 Gyr after the Big Bang. We find that at least two-thirds of massive galaxies have appeared since this era, but also that a significant fraction of them are already in place in the early Universe.